2013
DOI: 10.1186/1756-0500-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ attitudes towards privacy in a Nepalese public hospital: a cross-sectional survey

Abstract: BackgroundMany people in western countries assume that privacy and confidentiality are features of most medical consultations. However, in many developing countries consultations take place in a public setting where privacy is extremely limited. This is often said to be culturally acceptable but there is little research to determine if this is true. This research sought to determine the attitudes of patients in eastern Nepal towards privacy in consultations. A structured survey was administered to a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
(11 reference statements)
3
14
0
2
Order By: Relevance
“…Within this context, the age, gender and culture of the affected subjects can directly affect the communication dynamics. The results found corroborate studies in the literature in which the authors observed discomfort of the patient with nudity and body exposure and manipulation [ 6 7 , 14 15 ]. The patients reported that requesting permission to manipulate their body, to examine them or to perform other care/procedure shows consideration and attention on the part of the professional, which makes the patient feel valued and in control of the situation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Within this context, the age, gender and culture of the affected subjects can directly affect the communication dynamics. The results found corroborate studies in the literature in which the authors observed discomfort of the patient with nudity and body exposure and manipulation [ 6 7 , 14 15 ]. The patients reported that requesting permission to manipulate their body, to examine them or to perform other care/procedure shows consideration and attention on the part of the professional, which makes the patient feel valued and in control of the situation.…”
Section: Discussionsupporting
confidence: 90%
“…International studies [ 6 7 ] have demonstrated the same problems of invasion by healthcare providers as those raised in Brazilian studies and in the present one. Touching the patient’s possessions without permission, changing the bed side table to a position that cannot be reached, and raising or lowering the window blinds without consulting the patient are attitudes of the nursing staff that cause much discomfort.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In developed nations, healthcare professionals respect the privacy of patients and are empathetic to their patients [Moore and Chaudhary, 2013]. In developing nations, the excessive demand for medical services, poverty, and the shortage of trained medical professionals negatively influence privacy and empathy as well as the provision of prompt service to patients [Andaleeb, 2000[Andaleeb, , 2008Andaleeb, Siddiqui, and Khandakar, 2007;World Bank, 2004].…”
Section: How Is Mhealth Distinct From Other Healthcare Platforms In Dmentioning
confidence: 99%
“…The same study also showed that privacy and confidentiality were a major concern for people, especially younger patients. There are similar concerns about patient privacy and confidentiality in South-East Asia and the Middle East, but no studies have been conducted in this area (24).…”
Section: Discussionmentioning
confidence: 99%